ANALISIS DAMPAK KEPENDUDUKAN TERHADAP TINGKAT KRIMINALITAS DI PROVINSI BANTEN - Riny Handayani (Jurnal Administrasi Publik, 2017)
Problems of poverty, unemployment and population conditions such as Fertility, Mortality and Mobility / Population Migration contributes to the occurrence of social conflicts and criminality directly or indirectly. Criminality in the Province of Banten has increased significantly or reached 68 percent during the year 2014 compared to the year 2013. Increase in conventional and transnational criminality in the jurisdiction of Banten Police compared to last year referring data, crime in 2013 as many as 3,569 cases, while in 2014 increased to 5.857 case. of 5,857 cases that occurred in the Banten Police Region, as many as 2191 cases can be resolved. The number decreased compared to 2013, from 3,569 cases, 2,077 cases that can be resolved (Banten Police, 2015). Rapid population growth as a new province, high unemployment rate, education gap and inter-district / city, welfare gaps between districts / municipalities and crime prone areas are the background of this study. Using Ecological Theory of Crime (Meliala, 2011). result of analysis that from variable of Quality of Population which have strong role affecting crime incident is aspect of Population Density, Population Quantity variable is aspect of School Participation Rate of age 19-24 years, Availability of Health Facility and, Percentage of Open Unemployment Rate (TPT). As for the variable Mobility of People who have positively influenced strongly and significantly is the aspect of Migrsi Risen. The two main solutions to overcome this problem are consistent implementation of rules relating to population administration so that all residents, especially migrants, are well-regulated and equitable with development and provide employment in each region, especially villages or other small towns, so that the population density is not concentrated in one or some areas and to anticipate the crime caused by Migration.